Efektifitas Emotional Freedom Technique (EFT) Terhadap Penurunan Tingkat Depresi Pada Lansia - Emy Sutiyarsih; Sr. Felisitas A Sri S (coba, 2017)
Depression in eldery couldn’t be easily detected because physical complaint was more often than emotional complaint. In severe case, depression could cause suicidal behaviour (Irawan, 2013). Therefore, elderly need assistance to deal with depression, and Emotional Freedom Technique (EFT) is one of the solution. Research design is pre-experimental design, using pre-test and post-test design. Before intervention, Geriatric Depression Scale test were given to one group of elder people. EFT intervention were given two times for four weeks, and Geriatric Depression Scale test were tested after intervention. Population was elder people who fulfill inclusion criterias, and 30 elderly were obatained. The significancy result was 0,000 (α = 0,05), it could be inferred that EFT has a strong relationship to depression scale. EFT could significantly reduce depression scale in elderly, so it can bes used effectively.